Infant and young children complementary feeding practices in South Asian families: a systematic review. (November 2016) - Manikam, Logan; Dharmaratnam, Abina; Robinson, Alexandra; Prasad, Ankita; Kuah, Jia Ying; Stephenson, Lucy; Shafi, Taimur; Ahmed, Sonia; Lingam, Raghu; Lakhanpaul, Monica
Abstract: Background: Sub-optimum nutrition among children remains an important problem among South Asian families in the UK. Appropriate complementary feeding practices in the first 2 years of life greatly reduce the risk of obesity and stunting. The UK diaspora is hypothesised to have similar complementary feeding practices to their countries of origin (India, Pakistan, and Bangladesh); if so, this could inform practice in the UK via reverse translation of evidence. We aimed to undertake a systematic review and narrative synthesis of studies assessing complementary feeding practices, and the beliefs that underpin them, in children under 2 years old within South Asian families living in the UK, India, Pakistan, and Bangladesh. Methods: We searched Medline, Embase, Global Health, Web of Science, OVID Maternity and Infant Care, Cochrane Library, Popline, and WHO Global Health Library from Jan 1, 1990, to June 30, 2016. The eligibility criteria were all primary research studies on complementary feeding practices in South Asian children aged 0–2 years, their families, or both, restricted to the English language. The search terms used were "children", "feeding", and "Asians" with their derivatives. Study selection, data extraction, and quality appraisal (EPPI-Centre weight of evidence) were performed by two independent researchers in a narrative synthesis approach. This study is registered with PROSPERO, number CRD42014014025. Findings: From 45 702 studies identified, 157 descriptive studies (115 cross-sectional, 19 cohort, 14 qualitative, one case-control, and eight mixed studies) were included. Ten were from the UK, 17 Pakistan, 84 India, 43 Bangladesh, and three a combination of these countries. Despite adoption of the WHO Infant and Young Children Feeding Guidelines (particularly timing and food choice), substantial evidence of non-recommended complementary feeding practices was identified. Factors that affected these practices persisting after migration included bicultural issues or low acculturation levels and conflicting information between health professionals, extended family, and religious and community leaders. By contrast, barriers to enforcement of WHO-recommended complementary feeding practices in South Asian countries included early marriage, conflicts about best use of mother's time, rural life, short birth intervals, and poverty. Interpretation: This is the first systematic review, to our knowledge, to study complementary feeding practices across these countries. Similar themes were noted between UK families and countries of origin despite their receiving close National Health Service input from birth (eg, health visitors, general practitioners). This study will inform reverse translation of effective interventions to the UK from their countries of origin to improve complementary feeding practices in these communities. Funding: None.